Epistemologi Pendidikan Nilai Ditinjau dari Filsafat Pendidikan Islam Kontemporer - Maftukhah, Maftukhah; Nursikin, Mukh (Lembaga Yasin AlSys, 2023)
The purpose of writing this research is to conducted an in-depth analytical and research study of the epistemology of value education in terms of contemporary Islamic educational philosophy. This study used a type of qualitative research with an approach literature research methods. This article was an attempt from the epistymology of value education in caried out its transformation through contemporary Islamic educational philosophy. Contemporary Islamic educational philosophy showen that with the concept of epistimology, value education can lead to students who were broad-minded, knowledgeable, and independent. In an expression said that an educational renewal can be well directed if it was based on a solid educational philosophical and theoretical framework.